On sweet acorn (Quercus spp.) cake tradition in Italian cultural and ethnic islands - Pignone, Domenico; Laghetti, Gaetano (Genetic Resources and Crop Evolution, 2010)
The CNR-IGV, over the last 15 years, has organized and performed expeditions aimed at collecting germplasm and local knowledge on plants used by local populations in isolated areas, such as geographical islands, or local communities that for ethnic or cultural reasons have maintained to a certain degree their isolation from surrounding populations (cultural islands). In two such cultural islands (Bovesia, Calabria region, south-west mainland Italy, and Ogliastra, Sardinia island, Italy) a tradition regarding the use of acorns for preparing a cake was recorded. In Ogliastra, an elder lady still retains the knowledge regarding the collections, maintenance and utilization of acorns for preparing a cake, a knowledge once common and now quite completely disappeared. The present paper reports on the culture associated to acorn used as a food for humans.
Keywords: acorn; Cultural islands; Ethnobotany; Neglected food; Quercus spp.